Implementation of online education during the global Covid-19 pandemic: Prospects and challenges - Sri Haryati; Sukarno Sukarno; Sugeng Purwanto (LPMPP Universitas Negeri Yogyakarta, 2021)
Due to an abrupt outbreak of the global COVID-19 pandemic, the educational paradigm has to be shifted to a new era of online education at all levels while maintaining the Sustainable Development Goals (SDGs). The study aims to analyze the implementation of online education focusing on (1) institutional preparedness of digital infrastructure and (2) students' learning activities during the pandemic. An online survey (Google Survey) was conducted to collect the data, which were then qualitatively analyzed supported by data quantification in percentage. The findings indicate that the target schools managed to carry out online education in response to the government's social restriction. Online education has been implemented in three different contexts, depending on the types and strata of schools-fully, partially, and none of the two. This has opened up prospects and challenges to create different standpoints. The students learn through a variety of virtual learning activities, such as watching videos (YouTube or Teacher's presentation), completing quizzes, doing assignments, discussion via Google Meet, and the like depending on the class design.